Discontinuation of β-blocker therapy in stabilised patients after acute myocardial infarction (SMART-DECISION): rationale and design of the randomised controlled trial - Jin-Ok Jeong; Juhee Cho; Chang-Hwan Yoon; Sung Gyun Ahn; Cheol Woong Yu; Hyun Kuk Kim; Danbee Kang; Eliseo Guallar; Juwon Kim; Ki Hong Choi; Taek Kyu Park; Jeong Hoon Yang; et al. (BMJ Open)
Introduction There is a lack of evidence to support the effectiveness of prolonged β-blocker therapy after stabilisation of patients with acute myocardial infarction (AMI) without heart failure (HF) or left ventricular systolic dysfunction.Methods and analysis The SMart Angioplasty Research Team: DEcision on Medical Therapy in Patients with Coronary Artery DIsease or Structural Heart Disease Undergoing InterventiON (SMART-DECISION) trial is a multicentre, prospective, open-label, randomised, non-inferiority trial designed to determine whether discontinuing β-blocker therapy after ≥1 year of maintenance in stabilised patients after AMI is non-inferior to continuing it. Patients eligible for participation are those without HF or left ventricular systolic dysfunction (ejection fraction >40%) who have been continuing β-blocker therapy for ≥1 year after AMI. A total of 2540 patients will be randomised 1:1 to continuation of β-blocker therapy or not. Randomisation will be stratified according to the type of AMI (ie, ST-segment-elevation MI or non-ST-segment-elevation MI), type of β-blocker (carvedilol, bisoprolol, nebivolol or other) and participating centre. The primary study endpoint is a composite of all-cause death, MI and hospitalisation for HF over a median follow-up period of 3.5 years (minimum, 2.5 years; maximum, 4.5 years). Adverse effects related to β-blocker therapy, the occurrence of atrial fibrillation, medical costs and Patient-reported Outcomes Measurement Information system-29 questionnaire responses will also be collected as secondary endpoints.Ethics and dissemination Ethics approval for this study was granted by the Institutional Review Board of Samsung Medical Center (no. 2020-10-176). Informed consent is obtained from every participant before randomisation. The results of this study will be submitted for publication in international peer-reviewed journals and the key findings will be presented at international scientific conferences.Trial registration number ClinicalTrials.gov, NCT04769362.